Field trial for air entrained grout enriched roller compacted concrete - Musselman, E. S., author; Zimmer, G. J., author; Young, J. R., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Roller compacted concrete (RCC) is frequently used to armor earthen embankments for passing extreme floods and to construct gravity dams and stepped spillways. Early experience on RCC dam applications in the 1980s showed a tendency for seepage to develop along the lift lines. Therefore, RCC dam designers started including an upstream facing system as a watertight barrier. An alternative facing material that has been used extensively overseas and is starting to gain more widespread acceptance in the United States is Grout Enriched RCC (GERCC). The grout enriched method of face construction has been shown to be less expensive than other facing options, particularly on larger dam projects, and has also been used on exposed RCC embankment overtopping projects. However, in the United States, the use of GERCC technology has been fairly limited, primarily due to concern over the material's freeze-thaw resistance. The objective of this project is to develop a grout formulation and construction technique that allows the production of air entrained GERCC. The study includes four phases to systemically achieve this objective: (1) optimizing grout formulation, (2 and 3) evaluation of small scale laboratory samples of GERCC, and (4) conducting a field trial. This paper focuses on the final phase, a field trial conducted with ASI contractors at the Duck River Dam site located in Alabama. The results show that the adequate freeze thaw resistance can be attained by air entraining GERCC, but the results are very sensitive to the distribution of the grout through the RCC and adequate performance requires significant internal vibration.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: roller compacted concrete; overtopping protection; stepped spillways; freeze-thaw resistance